Conversations with Readers: An Interview with Daphne Marlatt - Curran, Beverley; Hirabayashi, Mitoko (Studies in Canadian Literature, 1999)
Daphne Marlatt speaks about her interest in conversation, oral culture, and the dialogic in writing. She describes her experiences collaborating with writers such as Betsy Warland and Nicole Brossard, arguing that writers always unintentionally collaborate with others. Marlatt speaks of herself as a feminist writer and resists defining women's writing. She speaks about Ana Historic as translation and as a narrative that negotiates space for stories forgotten or not yet imagined. She also discusses the woman-to-woman relationships in her novel Taken.